IDENTIFICATION OF THERMAL COMFORT CONDITIONS IN A RESIDENTIAL: A CASE STUDY OF A 2-STORY BALINESE CONTEMPORARY HOUSE IN BATUAN, GIANYAR, BALI - I Putu Weka Wendyputra; Kadek Wisnawa; Alvin Yesaya (Universitas Udayana, 2024)
Housing is a fundamental human need that requires to offer its occupants the best possible safety and comfort. The Gianyar district of Bali is now home to a disproportionate number of structures of the Bali architectural style. The thermal comfort of modern Bali buildings is the subject of the bare minimum research, which makes it crucial to determine the thermal comfort of these structures as a foundational knowledge and point of reference for thermal studies of comparable structures. Using Autodesk Ecotect Analysis 2011 software, the research was conducted by modeling spatial convenience and presenting quantitative descriptive data through data tabulation and graphics. The study's findings demonstrated that the Bali Contemporary Building Study facility in Mas Village, Gianyar, had thermal comfort levels that exceeded Indonesia's norms.